Enhancing Fifth-Grade Students’ Creativity in Visual Arts Learning Through Concrete Media: A Classroom Action Research Study - Arum Ariyanti; Andi Imrah Dewi; Kadek Hariana; Zulnuraini Zulnuraini; Kasmawati Kasmawati (MASI Mandiri Edukasi, 2026)
This study was motivated by the low level of students’ creativity in visual arts learning, particularly in understanding the principle of rhythm, which is still abstract and difficult for elementary school students to apply. The purpose of this study was to enhance fifth-grade students' creativity through concrete media in visual arts instruction, focusing on rhythm. This research employed a Classroom Action Research (CAR) approach conducted in two cycles, involving 22 fifth-grade students at SDN Biro, Palu City. Data were collected through observation and documentation, and analysed using descriptive quantitative techniques expressed in percentages. The results showed that students’ creativity improved from Cycle I to Cycle II, with the mastery percentage increasing from 68.18% in Cycle I to 86.36% In Cycle II. This improvement was reflected in students’ ability to develop ideas, create variations In form, demonstrate originality, and complete their drawings carefully. The findings indicate that the use of concrete media helps students understand the principle of rhythm through direct experiences of observing, trying, and organising visual patterns, encouraging active engagement and the gradual development of creativity. Therefore, concrete media is effective in elementary visual arts learning for enhancing students’ creativity in understanding the principle of rhythm.